Initial COVID-19-related restrictions (lockdown) in 2020 and birth outcomes in Switzerland: an observational study based on statistics of outpatient midwifery services (Swiss Medical Weekly, 2025)
AIMS: Heterogeneous results regarding changes in the risk of preterm births and other perinatal outcomes during COVID-19-related restrictions (lockdowns) have been reported. We aimed to investigate the association between adverse birth outcomes and the initial COVID-19-related lockdown in Switzerland in 2020.AIMS: Heterogeneous results regarding changes in the risk of preterm births and other perinatal outcomes during COVID-19-related restrictions (lockdowns) have been reported. We aimed to investigate the association between adverse birth outcomes and the initial COVID-19-related lockdown in Switzerland in 2020.METHODS: We included singleton births recorded in the nationwide statistics of outpatient midwifery services in Switzerland (2018–2020). Using logistic regression, we estimated odds ratios (ORs) with 95% confidence intervals (CIs) for the risk of three birth outcomes between 16 March 2020 and 10 May 2020 (lockdown period) compared to any time between January 2018 and the start of the lockdown period. The outcomes of interest were preterm birth (